ANALISIS KEBIJAKAN DESA MANDIRI ANGGUR MERAH UNTUK RAKYAT MENUJU SEJAHTERA (ANGGUR MERAH) DI PROVINSI NTT - NGATU, FERDINAND (Politika: Jurnal Ilmu Politik, 2014)
This research was conducted in South Central Timor. As an informant among them is the Governor of NTT, NTT Provincial Parliament, Head of Planning NTT Province, Regent TTS TTS Head of Planning, academics and bureaucrats are directly involved as well as understand and be able to provide information on policy formulation. Program policy formulation Desa Mandiri Anggur Merah was originally formulated by the Governor with Secretary Region NTT and NTT Head of Planning. Governor entrusted to the government officials to prepare the whole start of the program to design and supervise simultaneously evaluate this policy. Involvement in the policy on education Only limited monitoring is authorized to monitor and foster villages get help Independent Village Wine Red (1 SKPD oversee 2 village target ). Role of Village Community Empowerment Board (BPMD) or any other name that has direct contact with villagers and find out what the problem is in the village, were not involved in the process of formulating the problem. Development partnership programs with governments District/City views in the presence pereplikasian performed by all regencies/cities . The lack of delegation of authority given to the District/ City in the legitimacy of making such a program would not be implemented properly. Repair organizing primarily on education involvement NTT Province and Regency/ City regulation is clearly their respective roles, so that each can determine the function on education and tasks to be run, as well as being an active part in the implementation of the Desa Mandiri Anggur Merah to achieve goals. Giving duties and authority must function properly in order to avoid overlap between the Provincial Government and Regency/City .